NUTRITIONAL EVALUATION OF TEXTURISED MEAT FROM NEMIPTERUS JAPONICUS - NAIR, A LEKSHMY; STEPHEN, JOSE; SHENOY, A VASANTH; GOPAKUMAR, K (Fishery Technology, 2017)
Evaluation of the nutritional quality of texturised fish meat from threadfin bream (Nemipterus japonicus) is reported. Proximate composition and amino acid analysis showed that its protein content is very high with all the essential amino acids present in higher levels than those prescribed for man in the 1973 FAO/WHO amino acid scoring pattern. Lysine amounted to 11.0 g per 16 g N of which 75 percent is biologically available. Studies on ER and NPU also corroborate the excellent nutritional quality of the texturised meat.